(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Metabolic syndrome and insulin resistance has been the subject of much debate over the last two decades. Its pathophysiologycal basis, however, still remains to be clearly understood. Both genetic and environmental factors have been implicated in its pathogenesis. Mutation of genes encoding signal transduction molecules of insulin and acquired factors like aging, diets, physical activity, obesity and related molecular changes, dyslipidemia, hypertension and smoking were proposed by many groups. This review examined both acquired and genetic factors and discussed model of hormone-receptor-postreceptor interactions to explore the molecular basis of insulin resistance. DOI: http://dx.doi.org/10.3329/bjmb.v4i2.13773 Bangladesh J Med Biochem 2011; 4(2): 26-31